The Heterogeneity in the Relationships Between Psychological Drivers and Construction and Demolition Waste Management Intention and Behaviors Among Tunnel Construction Managers: Insights from Personality Profiles - Li, Yanjie; Yan, Guanfeng (Sustainability, 2025)
Effective tunnel construction and demolition (C&D) waste management is a critical issue in the context of sustainable development, and C&D waste management measures guided by 3R principles (Reduce, Reuse, and Recycle) comply with the circular economy. In this study, an extended theory of planned behavior model based on the existing literature was proposed to identify the drivers of tunnel construction managers’ intention to implement effective waste management measures; then, the respondents were classified into four groups according to personality traits to explore the effects of personality profile on the heterogeneity in relationships between psychological drivers and C&D waste management intention and behaviors. The results show that all TPB constructs, policies, and environmental concern are significant predictors of managers’ intention to manage C&D waste properly. Then, considerable variance in the driving effects of various psychological drivers across different groups is witnessed. For the positive and temperate participants, subjective norms and policies are the most effective driving factors. However, PBC and environmental concern show a stronger relationship with the conservative and introverted participants’ intentions to adopt effective waste management measures. The findings are beneficial to developing corresponding management measures to promote effective C&D waste management.